High-stability nylon tube quick connector material and preparation method thereof
Through graphene oxide and styrene grafting and freezing molding technology, high-strength, flame-retardant nylon tube quick plug joint material is formed, which solves the problem of insufficient strength and flame retardancy of nylon tubes, and achieves high reliability of the material and Sustainable production.
Patent Information
- Application Number
- CN202411381732.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-30
AI Technical Summary
Nylon pipes have poor flame retardancy and strong hydrophilicity, which leads to a decrease in strength and toughness, which is prone to bending and deforming, and cannot meet the needs of high-reliability industries.
Graphene oxide is combined with styrene and maleic anhydride for grafting to form graphene-styrene grafts, improving the interface compatibility between graphene oxide and nylon 66, and blending it with nylon 12, through Freeze-forming forms a three-dimensional aerogel structure, increasing flame retardant and mechanical properties.
It significantly improves the mechanical properties and flame retardant properties of nylon tube quick plug joint materials, avoids brittle cracks, meets the requirements of high-reliability industries, and is suitable for large-scale industrial production.
Smart Images

Figure CN119242029A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quick-plug connector materials, and in particular to a high-stability nylon tube quick-plug connector material and a preparation method thereof. Background Art
[0002] As an engineering plastic, nylon has many excellent properties such as excellent wear resistance, self-lubrication, mechanical properties, acid and alkali resistance, etc. It ranks first in the usage of engineering plastics in actual work and life. Nylon has excellent performance and many excellent properties that metal materials cannot compare with. It has been widely used in various fields at home and abroad, replacing metal materials used in many products, and its market share has greatly increased.
[0003] Quick connectors are connectors that quickly connect or disconnect pipes. They are widely used in the machinery and equipment industry. They are generally made of plastic, stainless steel, copper, aluminum, etc. Nylon tubes are corrosion-resistant, have a long service life, and are cheaper than metal tubes. They are also easy to install, reliable, and beautiful, and are widely used in quick-connect connectors.
[0004] However, due to the characteristics of nylon molecular structure, it not only has poor flame retardancy, but also has strong hydrophilicity, resulting in a significant decrease in the strength, toughness and mechanical strength of nylon tubes. At the same time, nylon tubes also have the defect of being easily bent and deformed, which cannot meet the requirements of mass production. They are prone to brittle cracking during long-term use and cannot meet the needs of industries with high reliability requirements. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a high-stability nylon tube quick-plug connector material and a preparation method thereof.
[0006] A high-stability nylon tube quick-plug connector material, whose raw materials include, by mass: 1250-100 parts of nylon, 10 parts of nylon 665, 1-3 parts of graphene oxide, 5-10 parts of styrene, 2-5 parts of maleic anhydride, 0.1-0.2 parts of initiator, 5-10 parts of polyethylene, 1-2 parts of polyethylene-maleic anhydride, 1-2 parts of triphenyl phosphite, 1-2 parts of lubricant, 1-2 parts of waterproofing agent, and 1-2 parts of antioxidant.
[0007] Preferably, the initiator is azobisisobutyronitrile.
[0008] Preferably, the lubricant is at least one of butyl stearate, ethylene bisstearamide, liquid paraffin, polyethylene wax, and polypropylene wax.
[0009] Preferably, the waterproofing agent is at least one of aluminum hydroxide, polysiloxane, glass microbeads, and calcium stearate.
[0010] Preferably, the antioxidant is at least one of antioxidant 1010 , antioxidant 168 , and antioxidant 1076 .
[0011] The preparation method of the above-mentioned high-stability nylon tube quick-plug connector material comprises the following steps:
[0012] S1, adding graphene oxide and styrene to a solvent and ultrasonically treating for 10-30 min, adding maleic anhydride and an initiator thereto, stirring at 60-80° C. for 1-2 h, removing the solvent, washing, and vacuum drying to obtain a graphene-styrene graft;
[0013] S2, adding nylon 66 to formic acid solution, stirring at 60-70°C for 1-2h, adding graphene-styrene grafted material thereto, stirring for 10-30min, cooling to -50--80°C, freezing for 1-2h, vacuum drying for 20-30h, with a vacuum degree of 10-50Pa, to obtain pretreated nylon 66;
[0014] S3, blending nylon 12 and pretreated nylon 66, extruding granulation, and drying; then adding polyethylene, polyethylene-maleic anhydride, triphenyl phosphite, lubricant, waterproofing agent, and antioxidant, melt-extruding, and pulling into shape.
[0015] Preferably, in S1, the ultrasonic frequency is 5-10 kHz.
[0016] Preferably, in S1, the solvent is toluene or xylene.
[0017] Preferably, in S3, the melting temperature is 200-230°C.
[0018] Preferably, in S3, during the traction forming process, the traction ratio is 1.1-1.2, and the shaping sleeve is evacuated to 0.01-0.05 MPa.
[0019] Beneficial effects:
[0020] If graphene oxide is added directly to nylon resin, it is very likely to exist in the form of stress concentration point defects, thereby greatly reducing the strength and flame retardant properties of the product.
[0021] The present invention can effectively avoid the agglomeration of graphene oxide by preparing graphene-styrene grafts, improve the interface between graphene oxide and nylon matrix, and enhance the mechanical properties of the composite material. At the same time, the graphene-styrene grafts can be combined with nylon 66 to form a three-dimensional aerogel structure, which has good dispersibility with nylon 12, high mutual bonding strength, and excellent mechanical properties of the product.
[0022] The present invention adopts graphene oxide in combination with styrene and maleic anhydride, and grafts them on the graphene surface through free radical polymerization, which can greatly improve the interface compatibility between graphene oxide and nylon 66. After nylon 66 is dissolved, it is combined with graphene-styrene grafts. Since the graphene-styrene grafts contain rich carboxyl groups, they can have strong interaction with the amide groups of nylon 66, and the two have a good combination effect. The pretreated nylon 66 formed by freezing treatment presents a three-dimensional aerogel structure, which is then combined with nylon 12. When subjected to external force, the load can be effectively transferred, and the bending performance of the product is significantly improved. At the same time, the impact performance is excellent. When subjected to external force, flexible deformation will occur effectively, and the toughening effect is excellent.
[0023] The present invention adopts freeze-setting to coat nylon 66 on the graphite oxide sheet structure, and a stable flame-retardant layer can be formed even at a low filling amount, so as to better exert the flame-retardant effect of the carbon layer. At the same time, it can be evenly dispersed in the nylon resin matrix, greatly improving the mechanical properties of the product; and the regular graphene oxide sheet structure increases the area of the carbon layer after combustion, and cooperates with triphenyl phosphite to dehydrate and catalyze into carbon, so the barrier effect is significant and the product has excellent fireproof performance.
[0024] Polyethylene can effectively improve the fluidity of nylon, and cooperate with the effect of graphene-styrene grafts to effectively improve the solubility between nylon and polyethylene. It not only enhances the toughness of the tube body, but also improves the fluidity and solubility of the system. Nylon tubes can be extruded smoothly, and the products have good molding stability.
[0025] The present invention pre-treats nylon 66 and then compounds it with nylon 12, polyethylene, polyethylene-maleic anhydride, triphenyl phosphite, etc. After molding, the product oxygen index can reach more than 38.6%, and the flame retardant grade can reach the V-0 grade of UL-94. At the same time, the mechanical strength is high, and brittle cracking is not easy to occur during long-term use. In addition, the process is simple, the reaction conditions are mild, and it is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a comparison chart of the tensile strength and elongation at break of the nylon tube quick-connect fitting materials obtained in Example 5 and Comparative Examples 1-2.
[0027] Figure 2 This is a comparison chart of the bending strength and bending modulus of the nylon tube quick-connect fitting materials obtained in Example 5 and Comparative Examples 1-2.
[0028] Figure 3 The water absorption and cantilever beam impact strength of the nylon tube quick-connect fitting materials obtained in Example 5 and Comparative Examples 1-2
[0029] Figure 4 This is a comparison chart of the oxygen index of the nylon tube quick-connect fitting materials obtained in Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0030] The present invention will be further explained below in conjunction with specific embodiments.
[0031] The nylon 66 used in the following is from DuPont of the United States, with the brand name 101L; the nylon 12 is from Evonik Degussa of Germany, with the brand name A1709P. The nylon 66 and nylon 12 used in the following need to be vacuum dried at 80°C for 10 hours before feeding.
[0032] Example 1
[0033] A high-stability nylon tube quick-plug connector material, whose raw materials include: 1250kg of nylon, 665kg of nylon, 1kg of graphene oxide, 5kg of styrene, 2kg of maleic anhydride, 0.1kg of azobisisobutyronitrile, 5kg of polyethylene, 1kg of polyethylene-maleic anhydride, 1kg of triphenyl phosphite, 1kg of butyl stearate, 1kg of aluminum hydroxide, and 10101kg of antioxidant.
[0034] The preparation method of the above-mentioned high-stability nylon tube quick-plug connector material comprises the following steps:
[0035] S1, adding graphene oxide and styrene to 50 kg of solvent and ultrasonically treating for 10 min at an ultrasonic frequency of 5 kHz, adding maleic anhydride and azobisisobutyronitrile, stirring at a temperature of 60 ° C for 1 h, removing the solvent, washing once with acetone, and vacuum drying to obtain a graphene-styrene graft;
[0036] S2, adding nylon 66 to 40kg of 70% formic acid solution, stirring at 60°C for 1h, adding graphene-styrene grafted product thereto, stirring for 10min, cooling to -50°C, freezing for 1h, vacuum drying for 20h, with a vacuum degree of 10Pa, to obtain pretreated nylon 66;
[0037] S3. Feed nylon 12 and pretreated nylon 66 into a twin-screw extruder for blending, extrusion, granulation and drying; add polyethylene, polyethylene-maleic anhydride, triphenyl phosphite, butyl stearate, aluminum hydroxide and antioxidant 1010, and feed into a single-screw extruder for melt extrusion, wherein the melt temperature is 200°C, the screw speed is 50r / min, and the traction molding is performed with a traction ratio of 1.1. The shaping sleeve is evacuated to 10kPa and cooled.
[0038] Example 2
[0039] A high-stability nylon tube quick-plug connector material, whose raw materials include: 12100kg of nylon, 6610kg of nylon, 3kg of graphene oxide, 10kg of styrene, 5kg of maleic anhydride, 0.2kg of azobisisobutyronitrile, 10kg of polyethylene, 2kg of polyethylene-maleic anhydride, 2kg of triphenyl phosphite, 2kg of ethylene bisstearamide, 2kg of polysiloxane, and 1682kg of antioxidant.
[0040] The preparation method of the above-mentioned high-stability nylon tube quick-plug connector material comprises the following steps:
[0041] S1, adding graphene oxide and styrene to 80 kg of solvent and ultrasonically treating for 30 min at an ultrasonic frequency of 10 kHz, adding maleic anhydride and azobisisobutyronitrile thereto, stirring at a temperature of 80 ° C for 2 h, removing the solvent, washing with acetone for 3 times, and vacuum drying to obtain a graphene-styrene graft;
[0042] S2, adding nylon 66 to 60kg of 80% formic acid solution by mass, stirring at 70°C for 2h, adding graphene-styrene grafted product thereto, stirring for 30min, cooling to -80°C, freezing for 2h, vacuum drying for 30h, and vacuum degree of 50Pa, to obtain pretreated nylon 66;
[0043] S3, send nylon 12 and pretreated nylon 66 into a twin-screw extruder for blending, extrusion, granulation, and drying; add polyethylene, polyethylene-maleic anhydride, triphenyl phosphite, ethylene bisstearamide, polysiloxane, and antioxidant 168, and send them into a single-screw extruder for melt extrusion, wherein the melt temperature is 230°C, the screw speed is 50-80r / min, and the traction molding is performed with a traction ratio of 1.2. The shaping sleeve is evacuated to 50kPa and cooled.
[0044] Example 3
[0045] A high-stability nylon tube quick-plug connector material, whose raw materials include: 1275kg of nylon, 669kg of nylon, 1.5kg of graphene oxide, 9kg of styrene, 3kg of maleic anhydride, 0.18kg of azobisisobutyronitrile, 7kg of polyethylene, 1.7kg of polyethylene-maleic anhydride, 1.2kg of triphenyl phosphite, 1.7kg of liquid paraffin, 1.4kg of glass microbeads, and 10761.6kg of antioxidant.
[0046] The preparation method of the above-mentioned high-stability nylon tube quick-plug connector material comprises the following steps:
[0047] S1, adding graphene oxide and styrene to 60 kg of solvent and ultrasonically treating for 25 min at an ultrasonic frequency of 6 kHz, adding maleic anhydride and azobisisobutyronitrile thereto, stirring at a temperature of 75 ° C for 80 min, removing the solvent, washing with acetone for 3 times, and vacuum drying to obtain a graphene-styrene graft;
[0048] S2, adding nylon 66 to 45kg of 77% formic acid solution, stirring at 62°C for 100min, adding graphene-styrene grafted product thereto, stirring for 15min, cooling to -70°C, freezing for 80min, vacuum drying for 28h, with a vacuum degree of 20Pa, to obtain pretreated nylon 66;
[0049] S3. Feed nylon 12 and pretreated nylon 66 into a twin-screw extruder for blending, extrusion, granulation and drying; add polyethylene, polyethylene-maleic anhydride, triphenyl phosphite, liquid paraffin, glass microbeads and antioxidant 1076 and feed into a single-screw extruder for melt extrusion, wherein the melt temperature is 220°C, the screw speed is 60r / min, and the traction molding is performed with a traction ratio of 1.17. The molding sleeve is evacuated to 20kPa and cooled.
[0050] Example 4
[0051] A high-stability nylon tube quick-plug connector material, whose raw materials include: 1295kg of nylon, 667kg of nylon, 2.5kg of graphene oxide, 7kg of styrene, 4kg of maleic anhydride, 0.12kg of azobisisobutyronitrile, 9kg of polyethylene, 1.3kg of polyethylene-maleic anhydride, 1.8kg of triphenyl phosphite, 1.3kg of polyethylene wax, 1.8kg of glass microbeads, and 1681.2kg of antioxidant.
[0052] The preparation method of the above-mentioned high-stability nylon tube quick-plug connector material comprises the following steps:
[0053] S1, adding graphene oxide and styrene to 70 kg of solvent and ultrasonically treating for 15 min at an ultrasonic frequency of 9 kHz, adding maleic anhydride and azobisisobutyronitrile thereto, stirring at a temperature of 65 ° C for 100 min, removing the solvent, washing once with acetone, and vacuum drying to obtain a graphene-styrene graft;
[0054] S2, adding nylon 66 to 55kg of formic acid solution with a mass fraction of 73%, stirring at a temperature of 68°C for 80min, adding graphene-styrene grafted product thereto, stirring for 25min, cooling to -60°C, freezing for 100min, and vacuum drying for 22h at a vacuum degree of 40Pa to obtain pretreated nylon 66;
[0055] S3. Feed nylon 12 and pretreated nylon 66 into a twin-screw extruder for blending, extrusion, granulation and drying; add polyethylene, polyethylene-maleic anhydride, triphenyl phosphite, polyethylene wax, glass beads and antioxidant 168 and feed into a single-screw extruder for melt extrusion, wherein the melt temperature is 210°C, the screw speed is 70r / min, and the traction molding is performed with a traction ratio of 1.12. The shaping sleeve is evacuated to 40kPa and cooled.
[0056] Example 5
[0057] A high-stability nylon tube quick-plug connector material, whose raw materials include: 1285kg of nylon, 668kg of nylon, 2kg of graphene oxide, 8kg of styrene, 3.5kg of maleic anhydride, 0.15kg of azobisisobutyronitrile, 8kg of polyethylene, 1.5kg of polyethylene-maleic anhydride, 1.5kg of triphenyl phosphite, 1.5kg of polypropylene wax, 1.6kg of glass microbeads, and 1.4kg of antioxidant 1010.
[0058] The preparation method of the above-mentioned high-stability nylon tube quick-plug connector material comprises the following steps:
[0059] S1, adding graphene oxide and styrene to 65 kg of solvent and ultrasonically treating for 20 min at an ultrasonic frequency of 7.5 kHz, adding maleic anhydride and azobisisobutyronitrile thereto, stirring at a temperature of 70° C. for 90 min, removing the solvent, washing with acetone twice, and vacuum drying to obtain a graphene-styrene graft;
[0060] S2, adding nylon 66 to 50kg of 75% formic acid solution, stirring at 65°C for 90min, adding graphene-styrene grafted product thereto, stirring for 20min, cooling to -65°C, freezing for 90min, vacuum drying for 25h, with a vacuum degree of 30Pa, to obtain pretreated nylon 66;
[0061] S3. Feed nylon 12 and pretreated nylon 66 into a twin-screw extruder for blending, extrusion, granulation and drying; add polyethylene, polyethylene-maleic anhydride, triphenyl phosphite, polypropylene wax, glass beads and antioxidant 1010 and feed into a single-screw extruder for melt extrusion, wherein the melt temperature is 215°C, the screw speed is 65r / min, and the traction molding is performed with a traction ratio of 1.15. The shaping sleeve is evacuated to 30kPa and cooled.
[0062] Comparative Example 1
[0063] A high-stability nylon tube quick-plug connector material, whose raw materials include: 1285kg of nylon, 668kg of nylon, 2kg of graphene oxide, 8kg of styrene, 3.5kg of maleic anhydride, 0.15kg of azobisisobutyronitrile, 8kg of polyethylene, 1.5kg of polyethylene-maleic anhydride, 1.5kg of triphenyl phosphite, 1.5kg of polypropylene wax, 1.6kg of glass microbeads, and 1.4kg of antioxidant 1010.
[0064] The preparation method of the above-mentioned high-stability nylon tube quick-plug connector material comprises the following steps:
[0065] S1, adding graphene oxide and styrene to 65 kg of solvent and ultrasonically treating for 20 min at an ultrasonic frequency of 7.5 kHz, adding maleic anhydride and azobisisobutyronitrile thereto, stirring at a temperature of 70° C. for 90 min, removing the solvent, washing with acetone twice, and vacuum drying to obtain a graphene-styrene graft;
[0066] S2. Feed nylon 12, nylon 66 and graphene-styrene grafts into a twin-screw extruder for blending, extrusion, granulation and drying; add polyethylene, polyethylene-maleic anhydride, triphenyl phosphite, polypropylene wax, glass beads and antioxidant 1010 and feed into a single-screw extruder for melt extrusion, wherein the melt temperature is 215°C, the screw speed is 65r / min, and the traction molding is performed with a traction ratio of 1.15. The shaping sleeve is evacuated to 30kPa and cooled.
[0067] Comparative Example 2
[0068] A high-stability nylon tube quick-plug connector material, whose raw materials include: 1285kg of nylon, 668kg of nylon, 2kg of graphene oxide, 8kg of polyethylene, 1.5kg of polyethylene-maleic anhydride, 1.5kg of triphenyl phosphite, 1.5kg of polypropylene wax, 1.6kg of glass microbeads, and 1.4kg of antioxidant 1010.
[0069] The preparation method of the above-mentioned high-stability nylon tube quick-plug connector material comprises the following steps:
[0070] S1, adding nylon 66 to 50kg of formic acid solution with a mass fraction of 75%, stirring at a temperature of 65°C for 90min, adding graphene thereto, stirring for 20min, cooling to -65°C, freezing for 90min, and vacuum drying for 25h at a vacuum degree of 30Pa to obtain pretreated nylon 66;
[0071] S2. Feed nylon 12 and pretreated nylon 66 into a twin-screw extruder for blending, extrusion, granulation and drying; add polyethylene, polyethylene-maleic anhydride, triphenyl phosphite, polypropylene wax, glass beads and antioxidant 1010 and feed into a single-screw extruder for melt extrusion, wherein the melt temperature is 215°C, the screw speed is 65r / min, and the traction molding is performed with a traction ratio of 1.15. The shaping sleeve is evacuated to 30kPa and cooled.
[0072] The performance tests of the nylon tube quick-plug connector materials obtained in Example 5 and Comparative Examples 1-2 were performed as follows:
[0073] (1) The tensile strength and elongation at break of each group of specimens were measured with reference to GB / T 1040.2-2022 “Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics”. The specimen size was 170 mm × 10 mm × 4 mm, the test rate was 50 mm / min, and the test temperature was room temperature.
[0074] (2) The flexural strength and flexural modulus of each group of specimens were measured with reference to GB / T 9341-2008 “Determination of flexural properties of plastics”. The specimen size was 80 mm × 10 mm × 4 mm, the test rate was 2 mm / min, the deflection was 6 mm, the specimen support span was 64 mm, and the test temperature was room temperature.
[0075] (3) The water absorption of each group of samples was measured with reference to GB / T 1034-2008 “Determination of water absorption of plastics”.
[0076] (4) The impact strength of each group of samples was measured with reference to GB / T 1843-2008 “Determination of cantilever beam impact strength of plastics”, using an A-type notch with a notch bottom radius of 0.25±0.05 mm, a pendulum energy of 2.75 J, and a sample size of 80 mm×10 mm×4 mm.
[0077] (5) The oxygen index of each group of samples was measured with reference to GB / T 2406.1-2008 “Determination of combustion behavior of plastics by oxygen index method Part 1: Guidance”.
[0078] like Figure 1 As shown, the tensile strength of the nylon tube quick connector material obtained in Example 5 is the highest, which is better than that of Comparative Examples 1-2 (P < 0.05). Although the elongation at break of the nylon tube quick connector material obtained in Example 5 is not significantly different from that of the other two groups (P > 0.05).
[0079] like Figure 2 As shown, the bending strength and bending modulus of the nylon tube quick connector material obtained in Example 5 are both the highest, which are better than those of Comparative Examples 1-2 (P < 0.05).
[0080] like Figure 3 As shown, the nylon tube quick-connect fitting material obtained in Example 5 has the lowest water absorption and the highest impact strength, both of which are better than those in Comparative Examples 1-2 (P < 0.05).
[0081] like Figure 4 As shown, the oxygen index of the nylon tube quick plug connector material obtained in Example 5 is the highest, which is better than that of Comparative Examples 1-2 (P<0.05), indicating that the flame retardant property of the nylon tube quick plug connector material obtained in Example 5 is the best.
[0082] The applicant believes that this is because the present invention can effectively avoid the agglomeration of graphene oxide by preparing graphene-styrene grafts, and can improve the interface between graphene oxide and nylon matrix, thereby enhancing the mechanical properties of the composite material. At the same time, the graphene-styrene grafts can be combined with nylon 66 to form a three-dimensional aerogel structure, which has good dispersibility with nylon 12, high mutual bonding strength, and excellent mechanical properties of the product. The present invention adopts graphene oxide in combination with styrene and maleic anhydride, and grafts them on the graphene surface through free radical polymerization, which can greatly improve the interface compatibility between graphene oxide and nylon 66. After nylon 66 is dissolved, it is combined with graphene-styrene grafts. Since the graphene-styrene grafts contain rich carboxyl groups, they can have strong interaction with the amide groups of nylon 66, and the two have a good combination effect. The pretreated nylon 66 formed by freezing treatment presents a three-dimensional aerogel structure, which is then combined with nylon 12. When subjected to external force, the load can be effectively transferred, and the bending performance of the product is significantly improved. At the same time, the impact performance is excellent. When subjected to external force, flexible deformation will occur effectively, and the toughening effect is excellent. The present invention adopts freeze-setting to coat nylon 66 on the graphite oxide sheet structure, and a stable flame-retardant layer can be formed even at a low filling amount, so as to better exert the flame-retardant effect of the carbon layer. At the same time, it can be evenly dispersed in the nylon resin matrix, greatly improving the mechanical properties of the product; and the regular graphene oxide sheet structure increases the area of the carbon layer after combustion, and cooperates with triphenyl phosphite to dehydrate and catalyze into carbon, so the barrier effect is significant and the product has excellent fireproof performance.
[0083] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A high-stability nylon tube quick-plug connector material, characterized in that: The raw materials include, by mass, 1250-100 parts of nylon, 10 parts of nylon 665, 1-3 parts of graphene oxide, 5-10 parts of styrene, 2-5 parts of maleic anhydride, 0.1-0.2 parts of initiator, 5-10 parts of polyethylene, 1-2 parts of polyethylene-maleic anhydride, 1-2 parts of triphenyl phosphite, 1-2 parts of lubricant, 1-2 parts of waterproofing agent and 1-2 parts of antioxidant.
2. The high-stability nylon tube quick-connect fitting material according to claim 1, characterized in that: The initiator is azobisisobutyronitrile.
3. The high-stability nylon tube quick-connect fitting material according to claim 1, characterized in that: The lubricant is at least one of butyl stearate, ethylene bisstearamide, liquid paraffin, polyethylene wax and polypropylene wax.
4. The high-stability nylon tube quick-connect fitting material according to claim 1, characterized in that: The waterproofing agent is at least one of aluminum hydroxide, polysiloxane, glass microbeads, and calcium stearate.
5. The high-stability nylon tube quick-connect fitting material according to claim 1, characterized in that: The antioxidant is at least one of antioxidant 1010, antioxidant 168, and antioxidant 1076.
6. A method for preparing the high-stability nylon tube quick-connect fitting material according to any one of claims 1 to 5, characterized in that: The steps include: S1, adding graphene oxide and styrene to a solvent and ultrasonically treating for 10-30 min, adding maleic anhydride and an initiator thereto, stirring at 60-80° C. for 1-2 h, removing the solvent, washing, and vacuum drying to obtain a graphene-styrene graft; S2, adding nylon 66 to formic acid solution, stirring at 60-70°C for 1-2h, adding graphene-styrene grafted material thereto, stirring for 10-30min, cooling to -50--80°C, freezing for 1-2h, vacuum drying for 20-30h, with a vacuum degree of 10-50Pa, to obtain pretreated nylon 66; S3, blending nylon 12 and pretreated nylon 66, extruding granulation, and drying; then adding polyethylene, polyethylene-maleic anhydride, triphenyl phosphite, lubricant, waterproofing agent, and antioxidant, melt-extruding, and pulling into shape.
7. The method for preparing the high-stability nylon tube quick-plug connector material according to claim 6, characterized in that: In S1, the ultrasound frequency is 5-10kHz.
8. The method for preparing the high-stability nylon tube quick-connect fitting material according to claim 6, characterized in that: In S1, the solvent is toluene or xylene.
9. The method for preparing the high-stability nylon tube quick-connect fitting material according to claim 6, characterized in that: In S3, the melting temperature is 200-230°C.
10. The method for preparing the high-stability nylon tube quick-connect fitting material according to claim 6, characterized in that: In S3, during the traction molding process, the traction ratio is 1.1-1.2, and the molding sleeve is evacuated to 0.01-0.05 MPa.
Citation Information
Patent Citations
Graphene and multiwalled carbon nanotube synergetic enhanced polymer fiber and preparation method thereof
CN104357941A
Oxidized graphene-reinforced nylon material as well as preparation method and application thereof
CN105038212A
Method for carrying out graft modification on graphene by virtue of styrene-maleic anhydride copolymer
CN106928413A
Low-water-adsorbing high-impact nylon composite material and preparation method thereof
CN109735097A
Polyamide resin composition
KR1020140005398A
Cited By
Ethylene glycol-resistant nylon material and preparation method thereof
CN119931334A